Analisis Keandalan Sistem Backup Power Menggunakan Generator dan UPS di Hotel 101 Bogor Suryakencana - Chandra Ramdan Kusumah; Dewi Rahmawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2026)
Reliability of electricity supply is a crucial factor for the hotel industry to maintain guest comfort and smooth operations. Hotel 101 Bogor Suryakancana relies on electricity from PLN as its primary source and a backup system consisting of a 750 kVA generator set and UPS. This study aims to analyze the reliability of the backup power system, including the Automatic Transfer Switch response time, the generator supply capacity, and the role of the UPS in transferring power sources during a PLN power outage. The results show that the load transfer time from PLN to the generator via the ATS averages 10 seconds, and the UPS is able to maintain uninterrupted power supply to the servers during the transfer. Calculations indicate that the generator capacity is sufficient to back up the entire hotel load with a nominal current of 1140.85 A and an ACB setting of 1711.28 A. This indicates that the backup power system has good reliability in maintaining continuity of electricity supply. Suggestions are given for routine testing and maintenance of the ATS and UPS systems to maintain optimal performance.